Student’s Mathematical Problem Solving Abilities Based on Emotional Quotient (EQ) - Nor Amalliyah; St. Budi Waluya; Arief Agoestanto (International Conference on Science, Education, and Technology, 2022)
Abstract. Problem solving ability is the ability of students to use their previous knowledge to solve problems encountered. Problem solving ability is one of the mathematical abilities that must be considered. This research is a qualitative descriptive study with the aim of describing students' mathematical problem solving abilities in terms of their emotional quotient. The research subjects consisted of 6 students, 2 students each with low, medium and high levels of emotional quotient. Based on the results of the study, it is known that students who have a low level of EQ cannot fulfill all the IDEAL problem solving steps. Students who have a medium level of EQ can fulfill all the IDEAL problem solving steps. Students who have a high level of EQ cannot fulfill the IDEAL problem solving step as a whole.